Towards realizing robotic potential in future intelligent food manufacturing systems. (August 2018) - Khan, Zeashan Hameed; Khalid, Azfar; Iqbal, Jamshed
Abstract: This paper provides a comprehensive review of the robotic potential that is foreseen by researchers in designing future food manufacturing plant. The present day food handling and packaging setup is limited in capacity and output due to manual processing. An optimized protocol to fetch various ingredients and shape them in a final product by passing through various stages in an automated processing plant while simultaneously ensuring high quality and hygienic environment is merely possible by using robotized processing. The review also highlights the possibilities and limitations of introducing these high technology robots in the food sector. A comparison of several robots from different classes is listed with major technical parameters. However, as predicted, a food cyber-physical production system (CPPS) visualizes a closed loop system for the desired output keeping in view various constraints and risks. Human machine interface (HMI) for these machines complies with the industrial safety standards to provide a fail safe production cycle. Various new horizons in research and development of food robots are also highlighted in the upcoming industrial paradigm.